Penalaran Deduktif Mahasiswa - Hastjarjo, Dicky (ANIMA Indonesian Psychological Journal, 2004)
The study was intended to determine the effects of different types of pragmatic schemas on the performance in conditional reasoning. Fifty seven freshmen of Faculty of Psychology, Gadjah Mada University (GMU), participated in the study. Deductive reasoning instrument consisted of twelve problems adapted from Klaczynski (1993) with minor revision. Arbitrer, pemission, and causal schemas were used in this study.The results show that most students failed to demonstrate conditional reasoning in all three types of pragmatic schemas. Permission schema was not solved better than the two other schemas. Penelitian bertujuan mengetahui pengaruh perbedaan skema pragmatis terhadap performans dalam penalaran kondisional. Lima puluh tujuh mahasiswa baru Fakultas Psikologi, Universitas Gadjah Mada menjadi subjek penelitian. Alat ukur penalaran deduktif terdiri atas 12 permasalahan yang diadaptasi dari Kiaczynski (1993). Skema arbitrer, permisi, dan kausal digunakan dalam penelitian ini. Hasilnya menunjukkan bahwa kemampuan penalaran kondisional mahasiswa tergolong rendah. Tidak ditemukan pengaruh perbedaan skema pragmatis terhadap penalaran kondisional mahasiswa.